Improving the Accounting of Administrative Expenses - Nizekeev Miyirman Baxit ugli (Research Parks Publishers, 2022)
The article studies the classification of expenses and the role of period expenses in its composition. As a result of the research, proposals were developed to reduce administrative and management costs and improve the accounting for expenses of the period.